1998
DOI: 10.1017/s0007114598001123
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of cadmium from wheat bran, sugar-beet fibre, carrots and cadmium chloride in the liver and kidneys of mice

Abstract: The gastrointestinal absorption and organ distribution of Cd after exposure for 9 weeks to three fibre-rich foodstuffs (wheat bran, sugar-beet fibre and carrots) were determined in mice. Groups of eight mice were given a diet containing 0·05 mg Cd/kg from wheat bran, sugar-beet fibre, carrots or CdCl 2 mixed in a semi-synthetic, low-Cd (<0·007 mg/kg) feed. A control group was fed on the low-Cd semi-synthetic feed. The water consumption, food consumption and the weight of the animals were monitored throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
5
23
0
Order By: Relevance
“…Several studies addressing this question have used grain-based diets, and these reports generally concur with our observation (Chan et al, 2000) that Cd incorporated into grain was accumulated similar to Cd added to grain (Moberg Wing, 1993;Lind et al, 1998), unless bran, from which Cd is less readily accumulated by the target organs, was included in the diet. Lind et al (1998) pointed out that bran often accounts for much of the phytate found in grain, and phytates are notoriously insoluble to digestion: It has been speculated that bran Cd might be mostly associated with phytate. If Cd phytate is absorbed less readily by the intestinal mucosa, or does not induce Cd-MT production, either of these could result in lower accumulation of Cd in the kidney.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies addressing this question have used grain-based diets, and these reports generally concur with our observation (Chan et al, 2000) that Cd incorporated into grain was accumulated similar to Cd added to grain (Moberg Wing, 1993;Lind et al, 1998), unless bran, from which Cd is less readily accumulated by the target organs, was included in the diet. Lind et al (1998) pointed out that bran often accounts for much of the phytate found in grain, and phytates are notoriously insoluble to digestion: It has been speculated that bran Cd might be mostly associated with phytate. If Cd phytate is absorbed less readily by the intestinal mucosa, or does not induce Cd-MT production, either of these could result in lower accumulation of Cd in the kidney.…”
Section: Discussionsupporting
confidence: 86%
“…b Feed intake was measured only for rats exposed to Cd in diet (controls were pairfed) c Cd intake of rats exposed to Cd in water and diet was calculated on the basis of the concentration of Cd in drinking water (0.3 mg Cd/l) and diet (0.4 mg Cd/kg), respectively 2002). This accounts for the use of Cd load in the liver and kidneys in the estimation of Cd uptake in the present study which is also in harmony with previous reports (Andersen et al 1992;Crowe and Morgan, 1997;Reeves and Vanderpool 1998;Lind et al 1995;Lind et al 1998). Thus the significantly (P \ 0.05) smaller combined Cd load of the liver plus that of the kidney of rats exposed to Cd via the experimental food-chain relative to those exposed to the element in drinking water for the same exposure periods (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, cadmium in the ® bre-rich fractions of wheat seems to be poorly bioavailable, due to the presence of high levels of zinc and phytates. A decrease in fractional absorption and accumulation of cadmium has been recorded in rats and mice fed with whole wheat grains or wheat bran with respect to other diets, the main reason being probably the formation of insoluble cadmium-phytate complexes (Moberg Wing 1993, Lind et al 1998.…”
Section: Resultsmentioning
confidence: 99%